2010
DOI: 10.1200/jco.2009.24.6389
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing a Diagnosis of Cancer: Where and How Does It Occur?

Abstract: A B S T R A C T PurposeWhile disclosing a cancer diagnosis to a patient is common practice, how it is disclosed and the impact it has on the patient are poorly understood. We examined how cancer diagnoses were first given to patients and the impact of different aspects of disclosure on patient satisfaction. Patients and MethodsWe provided a self-administered questionnaire to a total of 460 oncology patients of the National Cancer Institute (NCI) being treated at the National Institutes of Health (NIH) Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 21 publications
1
45
0
2
Order By: Relevance
“…While patients may have perceived this differently from how the diagnosis was actually delivered, a previous study reported that patients generally remember well how bad news was delivered . Other recent studies also observed that it remains common to deliver a cancer diagnosis by telephone: 18% of patients treated at the National Cancer Institute, and 25% to 50% of breast cancer patients in the United States received their diagnosis by telephone . However, patients prefer that their diagnosis is delivered during a personal conversation with the physician, during which the physician takes the time to discuss the condition and its consequences .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While patients may have perceived this differently from how the diagnosis was actually delivered, a previous study reported that patients generally remember well how bad news was delivered . Other recent studies also observed that it remains common to deliver a cancer diagnosis by telephone: 18% of patients treated at the National Cancer Institute, and 25% to 50% of breast cancer patients in the United States received their diagnosis by telephone . However, patients prefer that their diagnosis is delivered during a personal conversation with the physician, during which the physician takes the time to discuss the condition and its consequences .…”
Section: Discussionmentioning
confidence: 99%
“…The physician is the most important information source for prostate cancer patients . However, the main challenge faced by physicians involves when and how to deliver information related to prostate cancer in a manner that could diminish the psychosocial impact of the disease on the patient and their family members . Only a handful of studies have addressed how communication between the cancer patient and his/her physician can influence the patient's psychosocial adjustment to the disease, and how much the physician can and is expected to address and assist with the patient's psychosocial problems .…”
Section: Introductionmentioning
confidence: 99%
“…There are several publications on the topic of discussing cancer with the patient, such as that by Figg et al Others can be found by searching “physician” and “telling of bad news” or “disclosing a diagnosis of cancer.” This is also a moment that can be very badly handled by an inexperienced physician. If one is new to USGFNA, my advice would be to talk to a senior physician with experience in this area, whether that is another USGFNA pathologist, surgeon, or oncologist.…”
Section: Patient First Outpatient Clinic Attitudementioning
confidence: 99%
“…While the clinical knowledge of physicians is essential for good medical practice [1], the establishment of rapport between physicians and patients is an important factor contributing to patient satisfaction [2]. Poor communication is a significant predictor of patient complaints [3].…”
Section: Introductionmentioning
confidence: 99%